Sunnah Ghairu Tasyri'iyyah Yusuf Al-Qardhawi's Perspective and Its Relevance in Building Religious Moderation - Umi Sumbulah; Muhammad Zainuddin; Dio Alif Bawazier (Jurnal Living Hadis, 2022)
This article contains the moderate thoughts offered by Yusuf al-Qardhawi in understanding al-Sunnah. Sunnah is defined differently according to the scientific field emphasized. There is a definition of sunnah according to hadith experts, ushul fiqih experts and jurists. Sunnah in terms of content, there are sunnah qauliyyah, sunnah fi'liyah and taqririyah. The degree of sunnah is second only to the Qur'an. The division of the sunnah into tasyri'iyah and ghairu tasyri'iyah had its seeds in the classical period of the history of Islamic law. In the contemporary period the division of the sunnah into tasyri'iyah and ghairu tasyr'iyah got its perfect form. One of the scholars who developed the distribution of the sunnah is Yusuf al-Qardhawi. He emphasized a moderate understanding in understanding the sunnah. The trick is to divide the sunnah into sunnah tasyri'iyah and ghairu tasyri'iyah so as not to fall into an extreme understanding, as groups that claim sunnah in its various forms must be obeyed and groups that claim to separate worldly things from religions that are too extreme. This idea is an idea that is considered effective in balancing religious understanding so as not to become a group that is too extreme left or right. Especially in the midst of widespread intolerance, extremism and radicalism that is exposed to some contemporary Muslim society.